A Call for Change in the Public Education System in Nova Scotia - Hamilton-Hinch, Barbara-Ann; McIsaac, Jessie-Lee D.; Harkins, Mary-Jane; Jarvis, Sherry; LeBlanc, John C. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2021)
The United Nation’s International Decade for People of African Descent and Nova Scotia’s Ministry of African Nova Scotian Affairs recognize that students of African descent continue to experience inequities. As previous studies indicate, parents of Black learners identified that many educators lack knowledge and experience in understanding students of African descent.This study explored student achievement from the perspective of parents of children of African descent attending public schools in Nova Scotia. Participants included individual interviews and focus groups with parents from rural and urban areas. Based on Bronfenbrenner’s ecological theory framework, a thematic analysis of the data was conducted, a dominant storyline related to the families’ experiences in school and subsequent themes emerged: we are treated differently; we don’t feel connected; we know there are challenges: the resistance of parents; and we deal with injustices but persevere. These findings provide recommendations to improve the educational success for Black learners.